Permasalahan Lokasi Pedagang Kaki Lima dalam Ruang Perkotaan - Retno Widjajanti (TATALOKA, 2014)
Urban development is inseparable from the problem of the urban informal. The informal sector is a sector that will always grow and thrive. Various issues that arise in urban development is the problem of the location of the activity space street vendors (PKL) in the urban space. The problem of space activity occurs in the informal street vendors space settlements or urban space. PKL is one of the supporters of the activity in a public space that can be categorized as an 'activity support'. These activities tend to be located in a place according to its activity. Meanwhile, there is little discussion of urban street vendors in view space. Until now, the discussion is more to the economic, social and policy. In addition, many of the types of activities studied, space requirements, physical arrangement and the arrangement of the display / architectural aesthetics. The methodology used in conducting the study concerns the location of street vendors in the urban space using the method of literature revie. Given this method, can identify deficiencies / weaknesses of the informal sector theory and the theory of space to determine the location of street vendors in urban spaces. The conclusion of this research is to study the behavior of PKL space that affect the determination of the location of trade.Abstract : Urban development is inseparable from the problem of the urban informal. The informal sector is a sector that will always grow and thrive. Various issues that arise in urban development is the problem of the location of the activity space street vendors (PKL) in the urban space. The problem of space activity occurs in the informal street vendors space settlements or urban space. PKL is one of the supporters of the activity in a public space that can be categorized as an 'activity support'. These activities tend to be located in a place according to its activity. Meanwhile, there is little discussion of urban street vendors in view space. Until now, the discussion is more to the economic, social and policy. In addition, many of the types of activities studied, space requirements, physical arrangement and the arrangement of the display / architectural aesthetics. The methodology used in conducting the study concerns the location of street vendors in the urban space using the method of literature revie. Given this method, can identify deficiencies / weaknesses of the informal sector theory and the theory of space to determine the location of street vendors in urban spaces. The conclusion of this research is to study the behavior of PKL space that affect the determination of the location of trade.